The Role of Maternal Adverse Childhood Experiences and Race in Intergenerational High-Risk Smoking Behaviors. Issue 5 (11th April 2017) - Pear, Veronica A.; Petito, Lucia C.; Abrams, Barbara
Abstract: Introduction: A history of adversity in childhood is associated with cigarette smoking in adulthood, but there is less evidence for prenatal and next-generation offspring smoking. We investigated the association between maternal history of childhood adversity, pregnancy smoking, and early initiation of smoking in offspring, overall and by maternal race/ethnicity. Methods: Data on maternal childhood exposure to physical abuse, household alcohol abuse, and household mental illness, prenatal smoking behaviors, and offspring age of smoking initiation were analyzed from the US National Longitudinal Survey of Youth 1979 (NLSY79, n = 2999 mothers) and the NLSY79 Children and Young Adults Survey (NLSYCYA, n = 6596 children). Adjusted risk ratios were estimated using log-linear regression models. We assessed multiplicative interaction by race/ethnicity for all associations and a three-way interaction by maternal exposure to adversity and race/ethnicity for the association between prenatal and child smoking. Results: Maternal exposure to childhood physical abuse was significantly associated with 39% and 20% increased risks of prenatal smoking and child smoking, respectively. Household alcohol abuse was associated with significantly increased risks of 20% for prenatal smoking and 17% for child smoking. The prenatal smoking–child smoking relationship was modified by maternal exposure to household alcohol abuse and race. There were increased risks for Hispanic and white/other mothers as compared to the lowest risk group: black mothers who did not experience childhood household alcohol abuse. Conclusions: Mothers in this national sample who experienced adversity in childhood are more likely to smoke during pregnancy and their offspring are more likely to initiate smoking before age 18. Findings varied by type of adversity and race/ethnicity. Implications: These findings support the importance of a life-course approach to understanding prenatal and intergenerational smoking, and suggest that maternal early-life history is a potentially important risk factor that could be targeted with screening and interventions to reduce smoking in pregnant women and their children.